A tale of passion: New insights into entrepreneurship from a parenthood metaphor - Cardon, Melissa S.; Zietsma, Charlene; Saparito, Patrick; Matherne, Brett P.; Davis, Carolyn (Journal of Business Venturing, 2005)
While most organizational theories avoid emotion, many entrepreneurs act with emotion. Entrepreneurs often describe their businesses as their “babies,” expressing personal connection and even identification with their businesses. We therefore suggest that through exploring associated relational metaphors, we can gain additional insight into entrepreneurship. Specifically, we propose that parenting, with its nurturance, passion, or even neglect or abuse, offers a particularly fruitful metaphor for examining entrepreneurship that may better resonate with entrepreneurs themselves than does current theory. We examine various aspects of the progression of children and ventures, including nascent forms of entrepreneurship (gestation of babies), emergence, and postemergence activities, and highlight the ideas of passion, identification, attachment, and entrepreneurial context.